2018
DOI: 10.7202/1055117ar
|View full text |Cite
|
Sign up to set email alerts
|

Why Animal Welfare Is Not Biodiversity, Ecosystem Services, or Human Welfare: Toward a More Complete Assessment of Climate Impacts

Abstract: Ce document est protégé par la loi sur le droit d'auteur. L'utilisation des services d'Érudit (y compris la reproduction) est assujettie à sa politique d'utilisation que vous pouvez consulter en ligne. https://apropos.erudit.org/fr/usagers/politique-dutilisation/ Cet article est diffusé et préservé par Érudit.Érudit est un consortium interuniversitaire sans but lucratif composé de l'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
(15 reference statements)
1
5
0
Order By: Relevance
“…", suggested that there is no moral justification to ignore the suffering of an animal, and that this suffering should therefore enter into utilitarian calculation More generally, the ability to experience positive or negative states, such as happiness and suffering, is viewed as a fundamental criterion for moral consideration. This view is consistent with the conclusion of a large body of modern philosophers, regardless of their tradition, who have expressed an opinion on this matter (Carlier and Treich, 2020;McShane, 2018;Sebo, 2021). To describe this ability, a key word nowadays is "sentience".…”
Section: The Problemsupporting
confidence: 86%
See 1 more Smart Citation
“…", suggested that there is no moral justification to ignore the suffering of an animal, and that this suffering should therefore enter into utilitarian calculation More generally, the ability to experience positive or negative states, such as happiness and suffering, is viewed as a fundamental criterion for moral consideration. This view is consistent with the conclusion of a large body of modern philosophers, regardless of their tradition, who have expressed an opinion on this matter (Carlier and Treich, 2020;McShane, 2018;Sebo, 2021). To describe this ability, a key word nowadays is "sentience".…”
Section: The Problemsupporting
confidence: 86%
“…In particular, an important issue concerns our moral responsibility. Some would believe, for instance, that it is not our moral responsibility to protect wild animals, so that it is questionable to think that their welfare is our responsibility when designing a biodiversity policy (McShane, 2018).…”
Section: Normative Issuesmentioning
confidence: 99%
“…Indeed, such impacts raise considerable ethical and justicerelated considerations concerning the welfare of both the people who raise livestock and the animals themselves. 36 Such considerations need to play an increasing part in policy decisions about how to address the challenges of climate change adaptation, 37 particularly related to heat stress and the welfare of people and animals.…”
Section: Discussionmentioning
confidence: 99%
“…While previous research has found associations between lifetime classic psychedelic use and nature-relatedness, this study explored the associations between lifetime classic psychedelic use, ego dissolution during respondents' most intense experience using a classic psychedelic, and attitudes toward animals. Results suggest that classic psychedelic use and ego dissolution may facilitate a shift in human-animal relations toward less anthropocentric frameworks that acknowledge human-animal-environmental interconnectedness and enable more-than-human solidarity, which may subsequently lead to an increase in pro-environmental and sustainable attitudes and behaviors [35,36,[70][71][72]. More research is needed to better understand if, for whom, and under what circumstances classic psychedelic use might alter human-animal relations.…”
Section: Discussionmentioning
confidence: 99%